Superhuman with Artificial Intelligence: Classic Ambition Comes to Life - Chandra, Wie Wie (Sekolah Tinggi Teologi SAAT, 2021)
In his book, 2084: Artificial Intelligence and the Future of Humanity, John Lennox attempts to establish a biblical foundation for the two fundamental and existential problems of humanity, namely, where humans come from and where humans go. His book is divided into 13 chapters. Lennox devotes the first seven chapters to critiquing secular naturalists' responses to these two fundamental problems. He spends the following six chapters demonstrating how Christianity provides specific and more